Modulation of the photodynamic activity of a cinnamoyl-coumarin-RGD peptide conjugate via cucurbit[8]uril supramolecular assembly - Aspee-Lamas, A; Acuna-Castillo, C (ELSEVIER SCIENCE SA, 2026)
Peptide-based photosensitizers (PSs) have emerged as a powerful strategy to overcome the limitations of conventional PSs in photodynamic therapy (PDT), including poor water solubility, low selectivity, and limited phototoxic efficiency. In this study, we synthesized and characterized a novel cinnamoyl-coumarin-RGD peptide conjugate (PS-GG(KG)3G-RGD), designed to combine tumor-targeting capabilities, improved aqueous solubility, and photodynamic activity modulation by cucurbit[8]uril (CB [8]) complexation. Circular dichroism analysis showed a stable beta-sheet conformation and high-temperature stability for the conjugate. The photophysical behavior of PS-GG(KG)3G-RGD was evaluated in various solvents, revealing solvent-dependent excited-state dynamics, including the formation of internal charge transfer (ICT) and twisted internal charge transfer (TICT) excited states. Supramolecular complexation with CB[8] resulted in a 1:1 inclusion complex, confirmed by mass spectrometry and Job s plot; the fluorescence titration showed a high binding constant of (5.0 +/- 0.2) x 106 M-1 and stability under acidic conditions. Notably, PS-GG(KG)3G-RGD binding to CB[8] modulated fluorescence lifetime without significantly altering singlet oxygen generation. In vitro phototoxicity assays in MCF-7 breast cancer cell line demonstrated that the supramolecular assembly significantly enhanced phototoxicity in tumor cells. These findings support the potential of integrating supramolecular approaches with peptide conjugation to photosensitizers as a promising pathway toward the design of novel phototherapeutic agents.